Unlocking the Potential: A Review of Stem Cell Applications in Regenerative Medicine - Musyarifah, Zulda; Rahmadian, Rizki (Rumah Sakit Umum Pusat (RSUP) Dr. M. Djamil, 2024)
Background : Regenerative medicine stands at the forefront of transformative healthcare, offering innovative approaches to address tissue damage and degenerative conditions. Central to this paradigm is the profound impact of stem cell therapy, a dynamic and promising avenue within regenerative medicine. As we navigate the complexities of this evolving field, our systematic literature review seeks to unravel the diverse applications, breakthroughs, and challenges inherent in utilizing stem cells for regenerative purposes Methods : We searched in Science direct, Pubmed, NIH and another e-library with keyword stem cell, application and regenerative medicine. Our review aims to contribute to the ongoing narrative of stem cell therapy in regenerative medicine. Through this exploration, we aspire not only to enhance our understanding but also to guide future research endeavors and clinical applications in this dynamic and promising field. Result : We reviewed the article with the theme article is stem cell and regenerative medicine. Stem cell therapy consistently demonstrated remarkable efficacy in promoting tissue regeneration. Across applications, stem cells showcased a remarkable versatility in enhancing tissue-specific cell behavior and activating regenerative pathways. his versatility positions stem cells as a promising tool with broad applications in regenerative medicine. Conclusion : This review emphasize the versatility and efficacy of stem cells in diverse regenerative scenarios. Evaluating methodological quality and comparing studies reveal nuanced insights, guiding future research directions. This review provides a comprehensive understanding of the current landscape, paving the way for innovative approaches in regenerative medicine.